What affects the implementation of the renewable portfolio standard? An analysis of the four-party evolutionary game - Wang, Delu; Li, Chunxiao; Mao, Jinqi; Yang, Qing (Renewable energy, 2023)
The renewable portfolio standard (RPS) has become the primary policy tool to promote the transformation of the energy system. However, in the RPS implementation process, there are usually differences in the completion effects between provinces, so exploring the implementation influencing factors of RPS policy is significant. Given the diversity and complex interaction of subjects and strategies, we construct a four-party evolutionary game model including the central government (CG), local governments (LGs), power generation enterprises (PGEs), and power grid corporations (PGCs), and systematic analysis of the strategic behavior and main influencing factors. The results demonstrate that the CG, its strategy will change with the size of the incentive intensity. For LGs, its strategies are affected by factors such as regulatory costs, and unit fines, especially when the regulation cost is less than the penalty amount for the unfulfilled quota of PGCs; the LG is more inclined to choose strong regulation. For PGEs, the net income of different power generation forms will significantly impact the strategy of PGEs, and indirectly affect the strategy of LGs. For PGCs, increasing the incentive intensity, increasing the punishment of LG to PGCs, and reducing the operation cost of PGCs can help PGCs to complete the quota. [Display omitted]